Pengaruh Islamic Corporate Governance terhadap Islamic Corporate Social Responsibility dengan Shariah Compliance sebagai Variabel Pemoderasi Bank Umum Syariah Periode 2017-2023 - Suprihatin, Yulia; Hanif, Hernawan; Wijandari, Ana (Riwayat: Educational Journal of History and Humanities, 2025)
The development of Islamic banking in Indonesia plays a vital role in promoting societal welfare, as it operates in accordance with Sharia principles. To evaluate the performance of Corporate Social Responsibility (CSR), several indices have been developed, one of which is the Global Reporting Initiative (GRI) Index. However, the application of the GRI Index in Islamic Commercial Banks often faces challenges, as not all indicators fully align with Sharia principles. Therefore, Sharia-based institutions are encouraged to adopt the Islamic Social Reporting (ISR) indicators. Standards established by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the Islamic Financial Services Board (IFSB), which are in accordance with Sharia principles, should be taken into consideration. Using a quantitative approach, compliance with Sharia principles is considered a crucial factor in the relationship between Islamic Corporate Governance (ICG) and Islamic Corporate Social Responsibility (ICSR). Islamic Commercial Banks with a high level of Sharia compliance are expected to demonstrate greater consistency in implementing CSR activities that align with Islamic values. The sampling method employed in this study is purposive sampling, using annual reports of Islamic Commercial Banks from 2017 to 2023. Data analysis was conducted using content analysis techniques with SPSS version 22 as the measurement tool. The influence of Islamic Corporate Governance on Islamic Corporate Social Responsibility, with Sharia Compliance as a moderating variable, was measured, and it was found that Islamic Corporate Governance contributes 50.4% to Islamic Corporate Social Responsibility after accounting for the moderating effect of Sharia Compliance